Different effects of constitutive and induced microbiota modulation on microglia in a mouse model of Alzheimer’s disease - Charlotte Mezö; Nikolaos Dokalis; Omar Mossad; Ori Staszewski; Jana Neuber; Bahtiyar Yilmaz; Daniel Schnepf; Mercedes Gomez de Agüero; Stephanie C. Ganal-Vonarburg; Andrew J. Macpherson; Melanie Meyer-Luehmann; Peter Staeheli; et al. (Acta Neuropathologica Communications, 2020)
Abstract It was recently revealed that gut microbiota promote amyloid-beta (Aβ) burden in mouse models of Alzheimer’s disease (AD). However, the underlying mechanisms when using either germ-free (GF) housing conditions or treatments with antibiotics (ABX) remained unknown. In this study, we show that GF and ABX-treated 5x familial AD (5xFAD) mice developed attenuated hippocampal Aβ pathology and associated neuronal loss, and thereby delayed disease-related memory deficits. While Aβ production remained unaffected in both GF and ABX-treated 5xFAD mice, we noticed in GF 5xFAD mice enhanced microglial Aβ uptake at early stages of the disease compared to ABX-treated 5xFAD mice. Furthermore, RNA-sequencing of hippocampal microglia from SPF, GF and ABX-treated 5xFAD mice revealed distinct microbiota-dependent gene expression profiles associated with phagocytosis and altered microglial activation states. Taken together, we observed that constitutive or induced microbiota modulation in 5xFAD mice differentially controls microglial Aβ clearance mechanisms preventing neurodegeneration and cognitive deficits.